Blood–Brain Barrier Disruption as a Potential Target for Therapy in Posterior Reversible Encephalopathy Syndrome: Evidence From Multimodal MRI in Rats - Wang, Quanlai; Huang, Bin; Shen, Guiquan; Zeng, Yu; Chen, Zheng; Lu, Chunqiang; Lerner, Alexander; Gao, Bo (Frontiers in Neurology, 2019)
Background: To explore blood brain barrier (BBB) disruption in hypertensive posterior reversible encephalopathy syndrome (PRES). Methods: The hypertension rat models were successfully built and scanned on 7T micro-MRI. MRI parameter maps including apparent diffusion coefficient (ADC), T1 mapping and perfusion metrics including of cerebral blood volume (CBV), cerebral blood flow (CBF), mean transit time (MTT) and time to peak (TTP) were calculated. Results: The ADC values of the experimental group were higher than those of the control group both in cortex (P<0.01) and in subcortical (P<0.05). Voxel-wise analysis of ADC maps vasogenic brain edema mainly was shown in the posterior portion. The increase of CBV and CBF values were found in the cortex and subcortical regions of rats with acute hypertension. No correlation was found between perfusion metrics and MAP. The EB dye content was higher in the posterior brain region than anterior (P<0.05). Conclusions: Cerebral vasogenic edema resulting from acute hypertension supports the hypothesis of PRES as the result of BBB disruption, which maybe the potential therapeutic target for intervention. Key words: Posterior reversible encephalopathy syndrome; acute hypertension; blood brain barrier; MRI